Solomon Islands : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
The Solomon Islands's 2005 Article IV Consultation reports that the improvement in the economic performance registered after the arrival of the Australian-led intervention force in mid-2003 has continued. The projected deterioration in the external current account reflects investment-related imports, but reserve coverage should remain comfortable. The budget is projected to record a small deficit owing to one-off factors and higher spending as capacity and wages rise. With logging set to decline from its unsustainable level, much depends on new private activities coming on stream to replace lost incomes, exports, and government revenue.